Robustness evaluation of control algorithms for a long-stroke fast tool servo - Gong, Zheng; Huo, Dehong; Niu, Zengyuan; Chen, Wanqun; Cheng, Kai (Journal of manufacturing processes, 2022)
Fast tool servo (FTS) is an effective freeform surface machining technology in precision machining. The robustness of the FTS control algorithm is an important factor influencing the quality of machining. In this paper, an advanced PID control algorithm and a hybrid control algorithm are tested on a Lorentz force FTS. A mathematical simulation model is built according to the system characteristics. The model is verified by the system identification model and used for the simulation of the system's motion under disturbance. Simulation results show that the advanced PID control results in more significant differences in tracking error, amplitude error, and phase errors than the hybrid control. Four machining experiments are designed and conducted. The motion profile results from simulations and experiments show that the hybrid control (<0.5% tracking error) has better robustness than advanced PID control (>1.5% tracking error). In addition, the hybrid control exhibits rapid response speed. From the 3D profile of the machined microstructured surface, the hybrid control helps to achieve better form accuracy in the workpiece than the advanced PID control.